Specific stereoisomeric conformations determine the drug potency of cladosporin scaffold against malarial parasite - Das, Pronay; Babbar, Palak; Malhotra, Nipun; Sharma, Manmohan; Jachak, Goraknath R.; Gonnade, Rajesh G.; Shanmugam, Dhanasekaran; Harlos, Karl; Yogavel, Manickam; Sharma, Amit; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
The dependence of drug potency on diastereomeric configurations is a key facet. Using a novel general divergent synthetic route for a three-chiral center antimalarial natural product cladosporin, we built its complete library of stereoisomers (cladologs) and assessed their inhibitory potential using parasite-, enzyme-, and structure-based assays. We show that potency is manifest via tetrahyropyran ring conformations that are housed in the ribose binding pocket of parasite lysyl tRNA synthetase (KRS). Strikingly, drug potency between top and worst enantiomers varied 500-fold, and structures of KRS-cladolog complexes reveal that alterations at C3 and C10 are detrimental to drug potency whereas changes at C3 are sensed by rotameric flipping of glutamate 332. Given that scores of antimalarial and anti-infective drugs contain chiral centers, this work provides a new foundation for focusing on inhibitor stereochemistry as a facet of antimicrobial drug development.